IMPLEMENTATION FUZZY INFERENCE SYSTEM (FIS) FOR IDENTIFICATION IT ENTERPRENEURSHIPS BASED ON STUDENTS POTENTIAL - WIJI LESTARI; INDRA HASTUTI; SRI SUMARLINDA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to produce Fuzzy Inference System for mapping information technology (IT) entrepreneurship of students potential. This system application will acquire competence and knowledge of the IT entrepreneurs. This study will provide benefits to further increase the interest and motivation of students to become IT entrepreneurs. Results in the first phase is the mapping Entrepreneurships of information technology into the 5 types technopreneurships namely Software Application Developer, Data Analyst, Computer System & Network Engineer, Graphics Designer & Animator and Multimedia System Developer. Mapping based Academic Potential Test and Personal Characteristics (Entrepreneurships values). The results of the mapping used as domain expertise to develope systems based on Fuzzy Inference System. Result in second phase is the Mamdani Fuzzy Inference System with knowledge base, rule of system and architecture of systemfor identification IT Entrepreneurships potential of students based on Academic Potential Test and characteristics personal (entrepreneurships values).